Sejarah Dan Pemanfaatan Museum Benteng Vredeburg Sebagai Sumber Belajar Dan Wisata Edukasi - Siti Aisyah; Afifah Yulan Agustin; Masitoh Indarti; AbiyyuDzaky Fitrianto; Ramadhana; Nastiti Mufidah (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2026)
This study examines the role of the Benteng Vredeburg as an educational tourism destination that supports history learning. Education plays a crucial role in shaping historical awareness and national identity, yet history learning is often considered less engaging because it is dominated by theoretical explanations. Museums offer an alternative learning environment by providing direct interaction with historical objects and contextual experiences. This research aims to analyze how the Vredeburg Fortress Museum functions as a learning resource and how its facilities contribute to contextual and experiential learning. This study employed a qualitative descriptive approach. Data were collected through observation, in-depth interviews, and documentation involving museum managers, visitors, and participants in educational programs. The data were analyzed using the Miles and Huberman model, including data reduction, data display, and conclusion drawing. Data validity was ensured through source and technique triangulation. The results show that the museum has transformed from a colonial military fortress into an educational museum with significant historical and pedagogical value. The museum provides various learning media, including dioramas, artifacts, and interactive digital technologies that enhance visitor engagement. These features support contextual learning by connecting theoretical knowledge with real experiences. Therefore, the museum effectively supports meaningful history learning and strengthens historical awareness among visitors.